Ashish Kumar - let's learn, implement then understand Maths and Physics
Advertisements

यही जज्बा रहा तो मुश्किलों का हल भी निकलेगा
जमीं बंजर हुई तो क्या वहीं से जल भी निकलेगा
ना हो मायूस ना घबरा अंधेरों से मेरे साथी
इन्हीं रातों के दामन से सुनहरा कल भी निकलेगा

Logic for this lecture:

There are a lot of ways to perform substitution in integration. First way is to substitute the function only if its derivative is also occurring in question. Sometimes, you need to simplify the function to know whether you can apply substitution or not.

Advertisements

Questions Discussed in this lecture:
32. \(\int \frac{\cos 2x-\cos 2\alpha }{\cos x-\cos \alpha }  dx = 2(\sin x+x\cos \alpha )+C\)

33. \(\int \sin ^{-1} (\cos x) dx   = \frac{\pi x}{2} -\frac{x^{2} }{2} +C\)

Advertisements

34. \(\int \sin ^{2} (2x+5) dx = \frac{x}{2} -\frac{1}{8} \sin (4x+10)+C \)

35. \(\int \sin ^{3} (2x+1) dx   =  -\frac{1}{2} \cos (2x+1)+\frac{1}{6} \cos ^{3} (2x+1)+C\)

Advertisements

36. \(\int \sin ^{4}  x dx  =  \frac{3x}{8} -\frac{1}{4} \sin 2x+\frac{1}{32} \sin 4x+C\)

36. \(\int \sin ^{4}  x dx  =  \frac{3x}{8} -\frac{1}{4} \sin 2x+\frac{1}{32} \sin 4x+C\)

Advertisements

37. \(\int \sin x.\sin 2x dx \(\)   =  \(\)-\frac{1}{2} \left(\frac{\sin 3x}{3} -\sin x\right)+C\)

38. \(\int \sin 3x\cos 4x dx  =  -\frac{1}{14} \cos 7x+\frac{1}{2} \cos x+C\)

Advertisements

39. \(\int \tan ^{2} (2x-3) dx  =  \frac{1}{2} \tan (2x-3)-x+C \)

40. \(\int \sin ^{2} x \cos ^{4} x dx  =  \frac{1}{32} \left[2x+\frac{1}{2} \sin 2x-\frac{1}{2} \sin 4x-\frac{1}{6} \sin 6x\right]+C\)

Advertisements

41. \(\int \cos 2x\cos 4x\cos 6x dx = \frac{1}{4} \left[\frac{1}{12} \sin 12x+x+\frac{1}{8} \sin 8x+\frac{1}{4} \sin 4x\right]+C\)

43. \(\int \sin x\sin 2x\sin 3x dx  = \frac{1}{4} \left[\frac{1}{6} \cos 6x-\frac{1}{4} \cos 4x-\frac{1}{2} \cos 2x\right]+C\)

Advertisements

44. \(\int \tan ^{-1} \sqrt{\frac{1-\sin x}{1+\sin x} } dx = \frac{\pi }{4} x-\frac{x^{2} }{4} +C\)

45. \(\int \frac{e^{5log x} -e^{4log x} }{e^{3log x} -e^{2log x} } dx    =  \frac{x^{3} }{3} +C\)

Advertisements

46. \(\int \frac{dx}{\sqrt{1-2x} +\sqrt{3-2x} } = \frac{1}{6} (1- x)^{\frac{3}{2} } -\frac{1}{6} (3-2x)^{\frac{3}{2} } +C\)

47. \(\int \tan ^{-1} (cot x) dx =  \frac{\pi }{2} x-\frac{x^{2} }{2} +C\)

Advertisements

48. \(\int _{0}^{\pi } ( \sin ^{2} \frac{x}{2} -\cos ^{2} \frac{x}{2} ) dx  =  0\)

49. \(\int _{0}^{1}\frac{dx}{\sqrt{1+x} -\sqrt{x} } = \frac{4\sqrt{2} }{3} \)

Advertisements

This Post Has One Comment

Leave a Reply

Close Menu

New Report

Close